Evaluation Of Blood-Vegetable Waste Meal Fed with Or Without Grit to Broilers - Habiba, Z; Adedeji.M. O; Duweni.T; Adeniji, A.A (Zien Journals, 2021)
A total of one hundred and eighty (180) day old broiler chicks were used to evaluate the effect ofblood vegetable waste meal with or without grit supplementation on the performance of broilers.The dietsformulated had three inclusion levels of BVWM at 0, 7.5, and 15%, fed with two supplementation levels(with or without grit).The experimental animals were randomly distributed into six (6) dietary treatments.There were three replicates per treatment and ten (10) birds per replicate. Feed and water were provided adlibitum while standard poultry managements were strictly followed during the study. Data on differentperformance such as average daily fee intake, average daily weight gain and feed conversion ratio. It was a3X2 factorial experiment in a Completely Randomized Design (CRD). The experiment lasted for a period of8 weeks. The result showed that the experimental diet had significant effect on the final weight gain, dailyfeed intake, weight gain, feed conversion ratio, cost of feed per kg and profitability. The interaction betweenthe varying level of supplementation and no supplementation had significant effect (P <0.05) on feed to gainratio, but showed no significant difference in final weight, daily feed intake. This study shows that broilersfed 15% inclusion level of blood vegetable waste meal supplemented with grit at 5% had better performancewhen compared to 0% and 5% inclusion.
Keywords: supplementation; hundred; performance; broilers